CP-208 A decade of activity in clinical trials in a regional hospital pharmacy. (25th February 2017) - Duarte, A; Ramalhinho, AC; Morgado, S; Eusébio, I; Ribeiro, J; Moras, R; Fonseca, O; Mendes, M
Abstract : Background: Being responsible for the management of the investigational medicinal products (IMPs), pharmacists should create a descriptive standard operational procedure (SOP) to ensure the management of IMPs. Pharmacists should also implement good practices that promote therapeutic compliance to minimise the occurrence of errors and enhance the information available to the patient. Purpose: To describe the activity of a clinical trial service in a hospital pharmacy since 2006. Material and methods: Records of all clinical trials that took place in the hospital since 2006 were reviewed with evaluation of recently implemented methodologies. Results: Pharmacists created methodologies to keep accurate and up to date records to provide a full audit trail from reception until destruction of an IMP. They had written a clinical trial SOP and created four specific forms for each clinical trial: clinical trial summary; clinical trial diary; IMP stock control; and IMP accountability. To ensure the correct use and compliance of medication, four self-adhesive labels and leaflets with IMP information were developed. The growth of this service is evident in all pharmaceutical activities, with a maximum of IMP dispensing (150) and the number of ongoing patients (63) in August 2016. The maximum of IMP receipts (42) was dated to 2015, and there were 7 site selection visits which resulted in an increase in the number of initiation and monitoring visits. IMP dispensing is the activity that represents the largest number of pharmaceutical activities. The clinical trials were mainly phase III (78%), in haematology (30%) and cardiology (26%), with anticoagulant and antihypertensive drugs. In August 2016, the pharmacy took part in 11 clinical trials of 6 sponsors with 5 clinical services. Conclusion: The clinical trial service began in pharmacy in 2006 and methodologies were created over time to ensure a full audit trail of IMP management. Strategies were also implemented to ensure compliance with therapy, which has proved fundamental. This service has continuously grown, particularly since 2014 due to an increase in the number of clinical trials and the number of recruited patients which has brought challenges to our service that will continue to grow over time. No conflict of interest